THE INFLUENCE OF PARENTS ON STUDENTS’ CHOICE OF CAREER IN THESE PRESENT OCCUPATIONAL CHALLENGES. - Onoshakpokaiye, Odiri E. (Sanata Dharma University Yogyakarta, 2023)
Decision-making in choosing a career is a very vital aspect of life, and it determines what the person will be in future. If taken wrongly, it has a great effect on someone’s life which is why one needs to be careful in making a decision that pertains to a career. This career choice-making has become a major problem for students; most of them find it difficult to make the right decision; maybe they are not well guided. There is a need for parents to assist or guide their children when they are still young to enable them to make good decisions on career choices. Parents’ roles in deciding on a career are of great importance to the students, so this aspect should not be overlooked by parents. The study looked at the roles and influence of parents on students’ decisions on a career. One hundred and forty final-year diploma students were taken from Delta state university, Abraka, as the sample. One research question and one hypothesis were stated for the study. The study revealed that parents’ roles influence their children's career choices.